ANALYSIS OF PRESSURE LOSS COMPONENTS IN AN INDUSTRIAL EXTRACT DUCT SYSTEM (Journal of Engineering Studies and Research, 2016)
The frictional head loss and the loss through fittings are computed for branch duct runs of an industrial extract ventilation system. Results show increases of both of the aforementioned loss components with increase in duct length. Furthermore, the fraction of the total loss due to fittings decreases from 0.60 to 0.45, with a corresponding increase of the fraction due to friction (from 0.40 to 0.55).Representative fractions of head loss components, obtained in the manner of this study, are shown to facilitate loss estimates and extract fan selection.
Keywords: index duct runs; industrial ventilation; head loss components